Variable MR and pathologic patterns of hemorrhage after iodinated contrast infusion in MCA occlusion/reperfusion model. (29th November 2016) - Morales, Humberto; Lu, Aigang; Kurosawa, Yuko; Clark, Joseph F; Tomsick, Thomas
Abstract : Objective: To examine the hypothesis that IA reperfusion with iso-osmolar iodixanol, low-osmolar iopamidol, or saline causes different effects on MR signal changes and pathologic cut-brain section related to hemorrhagic transformation (HT) or iodinated radiographic contrast media (IRCM) deposition. Methods: Infarct was induced in 30 rats by middle cerebral artery suture occlusion. Reperfusion was performed after 5 hours with iso-osmolar iodixanol (n=9), low-osmolar iopamidol (n=12) or saline (n=9). MR images were obtained immediately after reperfusion and rats were sacrificed at 24 hours. Hypointense areas within the infarction on T2-weighted (T2-WI) or gradient echo (GRE) images were recorded and compared with HT on pathology. Fisher's exact test was used for proportions, and receiver operator curve analysis to evaluate MRI discrimination of hemorrhage. Results: Two types of HT were noted on pathology: confluent >0.2 mm petechial hemorrhage (PeH, 78%) or well-defined ≤0.2 mm hemorrhagic focus (HF, 22%). PeH was least common in the iodixanol subgroup (p<0.02). HF was more common in the IRCM group. Hypointense areas on T2-WI but not on GRE were significantly more common in the IRCM group (p<0.05). Hypointense areas on T2-WI and GRE discriminated HT (area under the curve: 0.714, p<0.002). Conclusions: IRCM and saline induced different MRI signal and pathologic patterns in our sample. We postulate that T2 hypointensity with no GRE hypointensity might be associated with IRCM deposition; and decreased frequency of PeH after iodixanol infusion and the presence of HF almost exclusively in the IRCM group might represent a direct/indirect effect of contrast infusion/deposition in the brain parenchyma after reperfusion. Our results support previous observations in IMS III and are hypothesis generating.